2008
DOI: 10.4049/jimmunol.181.6.4287
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Augments Neutrophil Migration through Enhancement of Adhesion Molecule Expression and Prevention of CXCR2 Internalization: Role of ATP-Sensitive Potassium Channels

Abstract: In this study, we have addressed the role of H2S in modulating neutrophil migration in either innate (LPS-challenged naive mice) or adaptive (methylated BSA (mBSA)-challenged immunized mice) immune responses. Treatment of mice with H2S synthesis inhibitors, dl-propargylglycine (PAG) or β-cyanoalanine, reduced neutrophil migration induced by LPS or methylated BSA (mBSA) into the peritoneal cavity and by mBSA into the femur/tibial joint of immunized mice. This effect was associated with decreased leukocyte rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 60 publications
1
52
0
Order By: Relevance
“…Hydrogen sulfide (H 2 S) is a gaseous transmitter involved in a multitude of physiologic functions, which includes immune and inflammatory processes (2) , perception, and pain mediation, as well as control of gastric mucosal integrity, vascular tone, and the control of gastrointestinal motility (4) . H 2 S is synthesized endogenously from L-cysteine, primarily via two enzymes: cystathionine-γ-lyase (CSE) and cystathionine-β-synthetase (CBS) (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a gaseous transmitter involved in a multitude of physiologic functions, which includes immune and inflammatory processes (2) , perception, and pain mediation, as well as control of gastric mucosal integrity, vascular tone, and the control of gastrointestinal motility (4) . H 2 S is synthesized endogenously from L-cysteine, primarily via two enzymes: cystathionine-γ-lyase (CSE) and cystathionine-β-synthetase (CBS) (9) .…”
Section: Introductionmentioning
confidence: 99%
“…16,29 Although whether PMN contain the same type of K ATP channel as pancreatic ␤ cells is not clear, there is well-established evidence that ATP-sensitive potassium channels play a critical role in modulating PMN inflammatory responses, including the enhanced expression of adhesion molecules and cell migration. 38,39 The molecular basis underlying the alteration of UCP2 level in PMN during chemotaxis process remains elusive. However, we speculate that 2 possible mechanisms may be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence was used to analyze GRK2 expression on blood neutrophils at 6 h postsurgery using anti-mouse GRK2 (Y137; Abcam) as the primary Ab, as previously described (14). Cell nuclei were stained with DAPI.…”
Section: Grk2 Immunofluorescencementioning
confidence: 99%
“…We and others have shown that the severity of sepsis in nondiabetic mice and patients is associated with reduced neutrophil migration to the focus of infection. This reduction in neutrophil migration is due to the internalization of the chemokine receptor CXCR2 and modulation of adhesion molecules expression on endothelium (13)(14)(15). CXCR2 internalization is associated with upregulation of G protein-coupled receptor kinase 2 (GRK2) expression in circulating neutrophils, which is, at least partially, mediated by systemic TLR2 and TLR4 activation (16)(17)(18).…”
mentioning
confidence: 99%